PENGGUNAAN BUKU SAKU SEBAGAI MEDIA UNTUK MENINGKATKAN PENGETAHUAN DAN KETERAMPILAN MENCUCI TANGAN ANAK - Taamu Taamu; Nurjannah - Nurjannah; Fitri - Wijayanti (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2020)
Background Background: One of the aspects fundamental that relates to the health of children is a problem of cleanliness hand. The behavior of a child who likes to play and often interact as directly with the environment of the potential for exposure to germs of bacteria that can stick in hand . By because it's cleanliness children's hands must always be kept clean . It is to do with accustom children to wash hands with the correct corresponding six- step systematic which is recommended by WHO with the use of soap on water flow. The importance of washing hands with properly in children can improve health, create the environment that is safe, and prevent the onset of various diseases such as diarrhea, diseases of skin, intestinal worms, an infection i tract respiratory above, and various kinds of disease infection more. Methods: This type of research is a Quasi experimental design with a pretest-posttest control group design. Research is conducted at the School of Basic State 33 Kendari subdistrict Abeli city of Kendari. The population is all students in the School of Basic State 33 Kendari in lesson 201 8/2019 which amounted to 349 people. The number of samples is 60 people. Withdrawal of the sample with the technique of simple random sampling. Results: The results showed that the descriptive majority of children in the treatment group that is 86,7% had knowledge that good about washing hands, and all the children that is 100% skilled wash hands after given the book pocket wash hands, whereas in the group k ontrol majority of children that 50% had knowledge that is enough about washing hands and the majority of children is 43.3% are not skilled in washing hands. Conclusion: based on the research results can be concluded that the provision of book pocket effectively improve knowl knowledge and skills of children Schools Elementary State 33 Kendari to wash hands. Keywords: Pocket Books, Skills, Washing Hands